2012
DOI: 10.1021/es201779p
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Mixing Processes in a Heterogeneous Sand Box Aquifer

Abstract: Mixing is increasingly recognized as a critical process for understanding and modeling reactive transport. Yet, mixing is hard to characterize because it depends nonlinearly on concentrations. Visualization of optical tracers in the laboratory at high spatial and temporal resolution can help advance the study of mixing processes. The solute distribution is obtained by analyzing the relationship between pixel intensity and tracer concentration. The problem with such techniques is that grain borders, light fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
(85 reference statements)
0
26
0
1
Order By: Relevance
“…Due to the small spatial scale at which mixing occurs, resolving steep concentration gradients at the field scale remains challenging despite the rapid development of improved monitoring techniques [e.g., Annable et al ., ; Anneser et al ., ; Devlin et al ., ]. Therefore, laboratory experiments [e.g., Castro‐Alcala et al ., ; de Anna et al ., ; Haberer et al ., ; Rolle et al ., ] and numerical simulations at multiple scales [e.g., de Dreuzy et al ., ; Herrera and Valocchi , ; Hochstetler et al ., ; Porta et al ., ; Rolle et al ., ; Tartakovsky et al ., ] are fundamental for the understanding of dilution in porous media. Most of these studies, however, focused on (quasi) two‐dimensional systems, while detailed experimental and modeling investigations in three‐dimensional domains are less common [e.g., Herrera et al ., ; Rashidi et al ., ; Silliman , ; Yoon and McKenna , ; Cirpka et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small spatial scale at which mixing occurs, resolving steep concentration gradients at the field scale remains challenging despite the rapid development of improved monitoring techniques [e.g., Annable et al ., ; Anneser et al ., ; Devlin et al ., ]. Therefore, laboratory experiments [e.g., Castro‐Alcala et al ., ; de Anna et al ., ; Haberer et al ., ; Rolle et al ., ] and numerical simulations at multiple scales [e.g., de Dreuzy et al ., ; Herrera and Valocchi , ; Hochstetler et al ., ; Porta et al ., ; Rolle et al ., ; Tartakovsky et al ., ] are fundamental for the understanding of dilution in porous media. Most of these studies, however, focused on (quasi) two‐dimensional systems, while detailed experimental and modeling investigations in three‐dimensional domains are less common [e.g., Herrera et al ., ; Rashidi et al ., ; Silliman , ; Yoon and McKenna , ; Cirpka et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Even without strongly defined preferential pathways, heterogeneity affects tracer transport, dispersion, and dilution. Castro‐Alcalá et al [] report visualization experiments of a (conservative) tracer migrating in a 2‐D flow cell containing a rectangular sand lens of fine sand (with relatively low K ) embedded in a coarse sand (higher K ) matrix. Careful image analysis demonstrated that the largest degree of mixing occurs along contacts between regions with different permeability and that rates of mixing and dilution evolve differently over time.…”
Section: Modelingmentioning
confidence: 99%
“…This often requires complete knowledge of the concentration over time and is impossible to monitor a field scale plume with sufficient resolution to fully resolve the detailed concentration field. The SDR can be applied to numerical and laboratory scale studies that quantify the spatio-temporal concentration field such as Gramling et al, [2002], Zinn et al, [2004], Acharya et al, [2007], Tartavkosky et al, [2008], and Castro-Alcala et al, [2012], but upscaling methods to connect the scales are needed. One simple method of doing so is outlined in section 4.4, but prior to considering that case we develop analytical tools for determining the effects that different limits on the problem domain will have on the dissipation rates.…”
Section: Dissipation Rates In Restricted Domainsmentioning
confidence: 99%